Biotechnology : (Blackwell Scientific Publications, 1985)
The purpose of this volume is to present a broad, informed view of contemporary biotechnology, a technology with ancient roots and enormous future potential. Written for both students of the subject and practitioners of research in specific aspects seeking a broader view, it is not intended as an advanced treatise but as an introduction to most major aspects of biotechnology.